Analysis of the Effectiveness of Human Resource Training and Development in Increasing the Competitiveness of MSMEs in Indonesia. - Syamsu Rijal; Muhlis (International Journal of Business and Quality Research, 2025)
This study aims to understand the role of training and human resource development (SDM) in enhancing the quality of micro, small, and medium enterprises (UMKM) in the digital era in the midst of the development of the digital era. This study uses the Systematic Literature Review (SLR) approach and content analysis on various empirical studies, this study evaluates the contribution of HR training to improving the competence of business actors, mastery of digital technology. The results of the analysis show that training programs that are contextually designed based on local needs, and combined with participatory methods and post-training mentoring have been proven to be effective in improving operational efficiency, product quality, and the adaptability of MSMEs to market changes. In addition, training that integrates digitalization also encourages the transformation of MSMEs into more modern and competitive businesses.